Factors Shaping Uptake of Antenatal Care in Surabaya Municipality, Indonesia: A Qualitative Study - Jones, Lisa; Damayanti, Nyoman Anita; Wiseman, Nicola; Harris, Neil (Kesmas, 2021)
Five focus group discussions (FGDs) with 61 pregnant women were conducted in June and July 2019 at primary health care (PHC) services within five urban areas of Surabaya, Indonesia. In addition, five semi-structured interviews with five midwives were carried out to explore the experiences of pregnant women accessing Antenatal Care (ANC) and the factors shaping uptake of ANC services. Data were audio-recorded, transcribed, and translated into English, and analyzed using thematic analysis. Findings from focus group discussions suggested that fears of negative diagnosis before initial ANC appointment and personal beliefs and myths surrounding pregnancy may delay uptake of ANC. Further, the influence of husbands, family, and friends and long waiting times with overcrowding leading to limited seating shaped timely access and return visits. In addition, feeling comfortable with the quality of the service and receiving a friendly service from the practitioners assisted women in feeling comfortable to return. Finally, midwives acknowledged feeling afraid of being referred to a hospital if deemed a high-risk pregnancy-shaped return ANC visits. The findings highlighted several factors needing to be addressed to increase the promptness of first ANC visits and ensure return visits to achieve great ANC coverage.